Strategi Komunikasi Fundraising Organisasi Kemasyarakatan - Turhamun Turhamun (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2020)
Fundraising is an activity to influence the community, both individuals and organizations to distribute funds or assistance both materially and non-material. Some funders currently still use sporadic and traditional methods so that fundraising often fails. This research is a library research. It aims to collect theories related to social organization fundraising strategies. Information data obtained by using literature searches, books, documentation, journals or other research results related to the object of research. Data analysis uses content analysis, namely drawing conclusions from the data that has been obtained by finding the core message of the theory objectively and systematically. The results of the study explained that there were three strategic social organization fundraising strategies, namely First; Communication strategy in fundamental must be directed at creating effective communication. Of course by fulfilling the communication elements as described above .. Second; Through rational and effective considerations, faundraising is directed at appropriate programs and according to community needs so that donors are willing to give donations. Third; It is hoped that Community Organizations will be able to diversify programs and methods of raising funds to attract potential donors more broadly and optimally. The organization should take a different and unique approach with the uniqueness of each organization. He can choose to use the right model, for example, face to face, direct mail, special events, and campaigns.